Case Studies Using Mine-Wide Monitoring Systems For Geotechnical Evaluations - John P. Dunford (International Conference on Ground Control in Mining, 1993)
U.S. Bureau of Mines researchers are investigating the ability of mine-wide monitoring systems already in place at many coal operations to provide a direct link between geotechnical instruments and the mine-wide monitoring console on the surface. This paper describes a number of field tests using instruments such as-string potentiometers to measure roof-to-floor closure and bed separation and pressure transducers to monitor pillar loading. The advantages of using existing systems include on-site data collection and analysis, real-time understanding of geological conditions, and long-term data recovery from areas that have become inaccessible to mine personnel. However, because data are generated constantly, large files develop very quickly. In many cases, the data are redundant, such as during times of reduced mining activity or in areas not yet in the vicinity of active mining. To reduce the volume of data, a software program was written that eliminates unnecessary readings and generates a more concise file that can be output to a mine-wide monitoring system, personal computer, or as hard copy.